High Fructose Intake and Adipogenesis - Hernández-Díazcouder, Adrián (Int J Mol Sci, 2019)
In modern societies, high fructose intake from sugar-sweetened beverages has contributed to obesity development. In the diet, sucrose and high fructose corn syrup are the main sources of fructose and can be metabolized in the intestine and transported into the systemic circulation. The liver can metabolize around 70% of fructose intake, while the remaining is metabolized by other tissues. Several tissues including adipose tissue express the main fructose transporter GLUT5. In vivo, chronic fructose intake promotes white adipose tissue accumulation through activating adipogenesis. In vitro experiments have also demonstrated that fructose alone induces adipogenesis by several mechanisms, including (1) triglycerides and very-low-density lipoprotein (VLDL) production by fructose metabolism, (2) the stimulation of glucocorticoid activation by increasing 11β-HSD1 activity, and (3) the promotion of reactive oxygen species (ROS) production through uric acid, NOX and XOR expression, mTORC1 signaling and Ang II induction. Moreover, it has been observed that fructose induces adipogenesis through increased ACE2 expression, which promotes high Ang-(1-7) levels, and through the inhibition of the thermogenic program by regulating Sirt1 and UCP1. Finally, microRNAs may also be involved in regulating adipogenesis in high fructose intake conditions. In this paper, we propose further directions for research in fructose participation in adipogenesis.